PEMBUATAN MI KERING DENGAN PENGGUNAAN TEPUNG LABU TANAH (Cucurbita moschata) - Dewi Yunita; Yanti Meldasari Lubis; Nurakmal ' (Universitas Riau, 2012)
This reseach purpose was to produce dried noodles by addition of pumpkin flour. The bestcombination of wheat flour and pumpkin flour with the best percentage of sodium tripoliphospate cannot only used for food diversification but also to replace the use of methanyl yellow as a colouringagent. This research was conducted using Randomized Block Design with two factors. The first factorwas the ratio between wheat and pumpkin flour (T) which consisted of three levels (T1 = 90:10, T2 =80:20, and T3 = 70:30) and the second factor was the percentage of sodium tripoliphosphate (K)which also consisted of three levels (K1 = 0.1%, K2 = 0.2%, and K3 = 0.3%).The best treatment wasshown in dried noodles with 20% of pumpkin flour and 0.2% of sodium tripoliphospate addition. Thisproduct has following physical characteristics: firmness (2585.57 g/cm3), stickiness (98.5 g/cm3),elasticity (0.52 g/cm3), cooking time (4.67 minutes), cooking loss (6.87%), and rehydration weight(219.62%). According the chemical analysis, this product has 9.85% of protein content, 2.44% of fatcontent, 2.20% of ash content, and 0.26 mg/100 ml of β-carotene rate.